Seamus Heaney and the end of Catholic Ireland - Quinlan, Kieran, 1945- (The Catholic University of America Press, 2020)
"Traces the similarities between religious developments in Ireland during the twentieth century and the evolution of Seamus Heaney's poetry and of his understanding of his religious self"--